2022
DOI: 10.1111/lam.13692
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazone analogues with promising antibacterial profiles: Synthesis, morphology, in vitro and in silico approaches

Abstract: Significance and Impact of the Study: Bacterial resistance development against commercial antibiotics has become one of the most significant global problems. There is a strong demand for the discovery of novel classes of antibiotics with high efficiency, low dose, no toxicity and affordable cost. According to the results described in this research, non-toxic nitrobenzylidene(quinazolin-4-yl)hydrazines (compounds 1b and 2b) can be considered promising medications for the treatment of infectious diseases owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…14,15 These NF derivatives containing typical hydrazide/hydrazone moieties may affect other infectious diseases, especially leishmaniasis, trypanosomiasis, tuberculosis, and cancer. [16][17][18][19][20][21] Several nitrofuran compounds with anti-tubercular activity have been reported. [19][20][21] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 These NF derivatives containing typical hydrazide/hydrazone moieties may affect other infectious diseases, especially leishmaniasis, trypanosomiasis, tuberculosis, and cancer. [16][17][18][19][20][21] Several nitrofuran compounds with anti-tubercular activity have been reported. [19][20][21] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been devoted to the synthesis of new hydrazones and to testing these molecules for antibacterial activity. [2][3][4][5] In this direction, Nabizadeh et al 6 reported nitro benzylidene (quinazoline-4-yl) hydrazine scaffold as an antimicrobial agent. Balasubramaniyan et al 7 reported the synthesis of 2r,6c-diaryl-3t-methylpiperidin-4-one arylsulphonylhydrazones and showed that they exhibit significant activity against bacteria.…”
Section: Introductionmentioning
confidence: 99%